Predicting fraudulent financial statement using cash flow shenanigans - Tarjo, Tarjo; Prasetyono, Prasetyono; Sakti, Eklamsia; Pujiono; Mat-Isa, Yusarina; Safkaur, Otniel (Business: Theory and Practice, 2023)
Detection of fraudulent financial stewardship in the cash flow section is an exciting thing and is rarely studied. This research empirically tests the discovery of fraudulent financial statements based on basic cash flow shenanigans. The sample of this study amounted to 470 data mining companies in Indonesia, Malaysia, China, and Japan. The analysis method used is a positive approach. The results show that all ratios used can predict fraudulent financial statements. Three ratios of cash flow shenanigans, namely change in receivable to cash flow operations, days payable outstanding, and change in inventory to cash flow operations, significantly affect the F-Score. Meanwhile, the six cash flow shenanigans ratios, namely cash flow operations to current liability, operating cash flow ratio, free cash flow, cash flow operations to total liability, days payable outstanding, and change in inventory to cash flow operations, have a significant effect on the M-Score.